2007
DOI: 10.1111/j.1467-7717.2007.01009.x
|View full text |Cite
|
Sign up to set email alerts
|

Operation Child‐ID: reunifying children with their legal guardians after Hurricane Katrina

Abstract: Children constitute a vulnerable population and special considerations are necessary in order to provide proper care for them during disasters. After disasters such as Hurricane Katrina, the rapid identification and protection of separated children and their reunification with legal guardians is necessary in order to minimise secondary injuries (i.e. physical and sexual abuse, neglect and abduction). At Camp Gruber, an Oklahoma shelter for Louisianans displaced by Hurricane Katrina, a survey tool was used to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…Despite extensive efforts put forth to reunite family members who were separated during the massive and chaotic evacuation that followed Katrina landfall,15 at the time of our post-Katrina screening, there were persistent reports in the school of a sizeable number of students who were still not living with their parents or their legal guardians 15 months after the hurricane. This suggests that many may have been forced to live for an extended period of time in neighbourhoods with neighbours with whom they may not feel socially connected, possibly without the supervisory care of an adult relative.…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive efforts put forth to reunite family members who were separated during the massive and chaotic evacuation that followed Katrina landfall,15 at the time of our post-Katrina screening, there were persistent reports in the school of a sizeable number of students who were still not living with their parents or their legal guardians 15 months after the hurricane. This suggests that many may have been forced to live for an extended period of time in neighbourhoods with neighbours with whom they may not feel socially connected, possibly without the supervisory care of an adult relative.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies focused on the vulnerability of children, in various disaster situations, because of their physiological, psychosocial, and cognitive differences from adults (Belfer, 2006;Brandenburg et al, 2007;Guha-Sapir et al, 2007;Javaid et al, 2011;Murray & Monteiro, 2012). The study showed that disaster vulnerability of children in Alabama and Texas are consistent with previous findings, in which a higher number of one to five year old children led to increased social vulnerability.…”
Section: Relationship Of Results To Previous Findingssupporting
confidence: 82%
“…In disaster situation children might be separated from family, therefore, quick identification of separated children as well as their reunification with family is indispensable to counteract secondary injuries, such as physical and sexual abuse, gender-based violence, exploitation, neglect, and abduction (Brandenburg et al, 2007;Javaid et al, 2011;Ritchie, Watson, & Friedman, 2006) . Some studies have also focused on the importance of infant feeding in postdisaster situations (Callaghan et al, 2007;Emily W. Harville et al, 2009).…”
Section: Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…21 , 22 Moreover, convincing lines of evidence regarding the impacts of the GEJE on child health are still lacking, despite the presence of great concern. 23 …”
Section: Introductionmentioning
confidence: 99%